1985
DOI: 10.1038/hdy.1985.118
|View full text |Cite
|
Sign up to set email alerts
|

Development of tolerance to ethanol in relation to the alcohol dehydrogenase locus in Drosophila melanogaster 1. Adult and egg-to-adult survival in relation to ADH activity

Abstract: Strains of Drosophila melanogaster homozygous either for the AdhF or the Adhs allele, were kept on food supplemented with ethanol. After 90 generations these strains (FFE and SSE) were tested for tolerance to ethanol and compared with control strains (FFN and SSN) from regular food. The E strains showed increased tolerance to ethanol, both in the adult and in the juvenile life stages. In the adults the increase in tolerance was not accompanied by an increase in ADH activity. In the juvenile life stages there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0
2

Year Published

1988
1988
1995
1995

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 48 publications
6
38
0
2
Order By: Relevance
“…Literature on the developmental rate of Adh genotypes comes from (i) selection experiments for developmental rate in polymorphic populations (Van Delden & Kamping, 1979;Cavener, 1983;, (ii) determination of genotype frequencies in fast and slow developing groups within polymorphic populations (Van Delden & Kamping, 1979;Marinkovié et. al., 1987), and (iii) measurement of developmental rate of homozygous strains (Kerver & Van Delden, 1985;Kohane & Parsons, 1986;Lzquierdo & Rubio, 1989). Although some of these studies revealed no differences in the rate of development between Adh genotypes, most studies indicated that AdhFF develops faster than in agreement with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Literature on the developmental rate of Adh genotypes comes from (i) selection experiments for developmental rate in polymorphic populations (Van Delden & Kamping, 1979;Cavener, 1983;, (ii) determination of genotype frequencies in fast and slow developing groups within polymorphic populations (Van Delden & Kamping, 1979;Marinkovié et. al., 1987), and (iii) measurement of developmental rate of homozygous strains (Kerver & Van Delden, 1985;Kohane & Parsons, 1986;Lzquierdo & Rubio, 1989). Although some of these studies revealed no differences in the rate of development between Adh genotypes, most studies indicated that AdhFF develops faster than in agreement with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…In general, ethanol as a selective agent can act either at the preadult or adult stages of Drosophila. It was shown earlier that in D. melanogaster, the adaptation to ethanol-rich media was mainly accomplished during the juvenile life stages and that the maternal ADH has a significant role in that process (Kerver & van Delden, 1985;Kerver & Rotman, 1987). In the virilis phylad of Drosophila, ADH is not maternally encoded and zygotic transcription of Adh is not seen until the 24th hour of embryogenesis (G. Ranganayakulu, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Methanol is a toxic alcohol to D. melanogaster (though it is not a substrate of ADH). Although methanol is not converted by ADH, the Ad/iF frequency Selection for an independent resistance to methanol (Van Delden and Kamping, 1983;Kerver and Van Delden, 1985) may have occurred, diminishing the fitness differences between Ad/i genotypes. Viability estimates for 0/0 and 0/ + on methanol (0.76 and 092 respectively) are lower than those for normal food (0.88 and 095 respectively) and indicate that these genotypes experience an initially greater disadvantage relative to +/+ than on normal food.…”
Section: Discussionmentioning
confidence: 99%